Dance Video Development Tutorial Betaja Dayak Kancing’k Meliau District for Art Culture Learning in Junior High School - Sesilia Wynni Wilhimina Tanema; Aloysius Mering; Indri Astuti (JETL (Journal of Education, Teaching and Learning), 2023)
The purpose of this study was to develop a video tutorial for the Betaja Dayak Kancing’k dance in the Meliau sub-district for learning Cultural Arts in Junior High School. To achieve the research objectives, the Research and Development (R&D) method of the ADDIE development model was used. With the ADDIE Development model, the research is carried out through the stages of (1) Analyze, (2) Design, (3) Develop, (4) Implement, and (5) Evaluate. This research was conducted at SMP Brother Pontianak 9th grade with 30 students and four validators, design experts, media experts, and dance learning materials experts. Data from expert instruments with qualitative and quantitative analysis as a whole from the results of data analysis (in the range of values 1-5) The tutorial video design was declared "Very feasible" with an average of 4.27. Likewise, the analysis of empirical test data with individual test procedures, small groups, and field tests. The 32 9th grade students of Brother Pontianak Junior High School with an average skill score of 88 in the "Very Good" category. The results of the effectiveness test in this study were the results of the dancing skills of the students, the results of which were 30 students, which showed that as many as 24 students got an average score of 85 and 6 students with an average of 65 students, it was concluded that the average result of students' dancing skills was 81.22 with a very good category. good. With the data obtained, video tutorials can be applied in junior high schools in learning arts and culture with dance material.